1987
DOI: 10.1093/carcin/8.9.1337
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in rat tissues by a series of homologous aliphatic nitrosamines ranging from N-nitrosodimethylamine to N-nitrosomethyldodecylamine

Abstract: Aliphatic iV-nitrosomethylalkylamines exhibit a remarkable organ specificity in rats, the principal targets for tumour induction being liver, oesophagus, urinary bladder and lung. We have determined the extent of DNA methylation in these tissues following a single oral dose (0.1 mmol/kg; 6 h survival) of each of 12 homologues, ranging from N-nitrosodimethyiamlne (Cl) to A4utrosomethyldodecylamine (C12). Methylpurines (7-and O*-methylguanine) were determined by cation exchange HPLC with fluorescence detection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…The first such experiment involved the coadministration of ethanol with NMEA which decreased the liver/esophagus ratio of 7-methylguanine adducts present 4 h after dosing (von Hole et al 1986b), which may have been due to the known inhibitory effects of ethanol on hepatic cytochrome P-450 enzyme activity (Sohn et al 1987). The other in vivo study (von Hofe et al 1987) showed that the levels of methylation of hepatic DNA decreased progressively in the homo-logous series from NDMA to N-nitrosomethylpentylamine while methylation in the esophagus increased, suggesting that enzymes in the esophagus may receive larger amounts of certain compounds. However, based on the present observations it seems that alternative mechanisms should be considered.…”
Section: Discussionmentioning
confidence: 96%
“…The first such experiment involved the coadministration of ethanol with NMEA which decreased the liver/esophagus ratio of 7-methylguanine adducts present 4 h after dosing (von Hole et al 1986b), which may have been due to the known inhibitory effects of ethanol on hepatic cytochrome P-450 enzyme activity (Sohn et al 1987). The other in vivo study (von Hofe et al 1987) showed that the levels of methylation of hepatic DNA decreased progressively in the homo-logous series from NDMA to N-nitrosomethylpentylamine while methylation in the esophagus increased, suggesting that enzymes in the esophagus may receive larger amounts of certain compounds. However, based on the present observations it seems that alternative mechanisms should be considered.…”
Section: Discussionmentioning
confidence: 96%
“…( 24 ) In contrast, curcumin increased large intestinal CYP2B1 and the mutagenic activation of NMBA and DMN. Together with the findings that high levels of esophageal DNA alkylation are induced by NOC, ( 8,12,13 ) and DNA methylation by NMBA and N ‐nitrosomethyl‐ n ‐butylamine in rats occurs to a higher extent in esophagus than in liver, ( 66 ) it suggests that modification of metabolic activation of NOC by the target organ plays a critical role in chemoprevention of NOC‐induced carcinogenesis in rats. It has been reported that curcumin inhibits the expression of c‐Jun and c‐Fos/AP‐1, ( 67 ) a transcriptional factor that plays an important role in the expressions of CYP2B1/2 ( 68 ) and CYP2E1, ( 69 ) but not CYP1A, ( 70 ) and 3 A, suggesting that the suppression of AP‐1‐induced transcription by curcumin might produce a decrease in CYP2B1 and 2E1 expressions in the esophagus and stomach.…”
Section: Discussionmentioning
confidence: 73%
“…( 11 ) These findings indicate the importance of metabolic activation of NMBA by the target organ and/or liver during the initiation phase, and some NOC are known to be metabolized in the esophagus at a relatively high rate, often leading to high levels of esophageal DNA alkylation. ( 8,12,13 ) The total CYP content of the esophagus microsomes is only 7% of that of liver microsomes, ( 14 ) but little is known about the expression of CYP species in rat esophagus; CYP1A1 and 2A3 proteins are constitutively expressed in rat esophagus microsomes, but CYP2B1/2, 2E1 and 3A2 proteins are not. ( 14–16 ) We have recently shown that NMBA is mutagenetically activated by hepatic CYP2B1 and 2B2, but not CYP2E1, in rats.…”
mentioning
confidence: 99%
“…Since rat esophagus appears to be particularly vulnerable to die carcinogenic effects of this methylating agent (4), the increased potency of NEMA-d 3 relative to NEMA in that organ would be explained if die extent of this deuterium-induced metabolic switching were sufficient to cause increased DNA mediylation in me esophagus. We have previously shown that NEMA mediylates, ethylates and 2-hydroxyediylates DNA of various organs in the rat (4)(5)(6). To test whether (3-deuteration does cause a shift in the profile of DNA adducts, we have now measured the extent of DNA alkylation in various target and nontarget organs of adult male Fischer 344 rats following exposure to single doses of N-nitroso([2-D 3 ]ethyl)methylamine (NEMA-d 3 )…”
Section: Introductionmentioning
confidence: 99%